Psychosocial predictors of weight bias among undergraduate students of Karachi, Pakistan - Roha S Memon; Mahnoor Y Shaikh; Asim Shaikh; Rohan K Ochani (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Weight bias refers to negative attitudes towards individuals based on their body weight perceived from their physique. The rising prevalence of this kind of discrimination has raised concerns about its effects on the physical and mental health of its victims. Overweight individuals are especially affected leading to a higher incidence of depression and anxiety among them. While there is an abundance of data concerning this problem in the west, barely any data exists in Pakistan. # Methods In January 2018, we conducted a cross-sectional study to assess both the psychological and social reasons for weight bias prevalent in the undergraduate students of Karachi. Undergraduate students from Karachi were included in the study, primarily medical students. Data was collected using a pre-specified questionnaire. Data were analyzed using Statistical Package for the Social Sciences program. # Results Out of the 399 individuals who were included in the study, 68.4% (n=273) were females. An overwhelming majority (72.2%, n=288) believed overweight people were lazy while 57.1% (n=228) admitted to having been body-shamed. One-third (33.3%, n=133) believed physique is important for success, yet, only 20.6% (n=82) idolized physical features of media personalities. Females were more likely to be criticized for their weight (*P*=0.037) and to be pressurized to lose weight by their families (*P*=0.04). On the other hand, males were more likely to mock people for their weight (*P*\<0.001), keep a record of their exercise (*P*=0.002) and to experience euphoric feelings during exercise (*P*=0.025). # Conclusions Reductions in weight bias at the population level is a necessity since weight-related issues have found to be associated with the population's mental and physical well-being. Studies that test the impact of new strategies eradicating negative attitudes towards overweight individuals are needed.